HIV/AIDS : The Impact on Poverty and Inequality - Haacker, Markus (IMF Working Papers; Working Paper ;, 2006)
Using available data on the distribution of HIV/AIDS prevalence across population groups for four sub-Saharan African countries and transposing this information to household income and expenditure surveys, we simulate the impact of HIV/AIDS on poverty and inequality. We find that the epidemic lowers average income and increases poverty, and that the jump in poverty is larger than expected from the fall in average income. This disproportionate increase in poverty reflects the large share of the population living on the threshold of poverty and the higher HIV prevalence rates in those segments of the population.